Translabial ultrasound for pelvic organ prolapse - Manal Ali Alqahtani; Sa Ra Lee (Korean Society of Obstetrics and Gynecology, 2023)
Pelvic organ prolapse (POP) is a significant public health concern in women and a common cause of gynecological surgery in elderly women. The prevalence of POP has increased with an increase in the aging population. POP is usually diagnosed based on pelvic examination. However, an imaging study may be necessary for more accurate diagnosis. Translabial ultrasound (TLUS) was used to assess diverse types of POP, particularly posterior-compartment POP. It is beneficial to distinguish between true and false rectocele, and detect the rectocele as clinically apparent. TLUS can also establish whether the underlying cause is a problem of the rectovaginal septum, perineal hypermobility, or isolated enterocele. TLUS also plays a role in differentiating POP from conditions that mimic POP. It is a simple, inexpensive, and non-harmful diagnostic modality that is appropriate for most gynecologic clinics.